Theoretical approaches to transdisciplinarity for an integral educational and health practice (Papeles, 2026)
Introduction: Transdisciplinarity as an alternative approach transcends all routine educational practices, which determine problem-solving from a single perspective. Given its importance in a complex world that requires comprehensiveness, interconnectedness, and contextualization, a systematic study was conducted to investigate how transdisciplinarity has been addressed in the education and health sectors. Methodology: It was developed using a qualitative and bibliographic approach, based on the consultation, analysis, and interpretation of 52 research studies published between 2006 and 2025 in high-impact databases and institutional repositories. Results and discussion: The results showed that, in the education sector, transdisciplinary curricula enable the development of political subjects capable of transforming their development scenarios and thus achieving sustainability. Meanwhile, in the health sector, transdisciplinary training of clinical staff is essential for a comprehensive approach to disease and for multidisciplinary research into public health phenomena. Conclusions: Transdisciplinarity drives an integral practice in education and health through document updating, the cross-cutting integration of knowledge, and the use of innovative tools, aimed at training professionals who are both ethical and capable of leadership.
Keywords: Transdisciplinarity; educational practice; integration studies; health services; professional training